Land titling program and farmland rental market participation in China: Evidence from pilot provinces. (May 2018) - Wang, Yahui; Li, Xiubin; Li, Wei; Tan, Minghong
Highlights: High transaction costs were caused by the incompleteness and instability of land property rights. Land titling program was implemented by the central government in China since 2008. The proportion of people leasing farmland increased by approximately 3.9%, while the rent received increased by about one quarter due to the implementation of land titling program. The effects of this program varied across rigions and the hysteresis of land titling was significant. Abstract: Because of the incompleteness and instability of property rights, high transaction costs have hindered the development of the farmland rental market in China and reduced the efficiency of resource allocation. In an attempt to remedy this, a land titling program (LTP) that removed the obstacles caused by ambiguous property rights was proposed by the Chinese Central Government in 2008, and was implemented as a series of pilot projects in several provinces. We developed a series of econometric models using data from the 2012 China Health and Retirement Longitudinal Study (CHARLS) to quantitatively estimate the impact of this program on the farmland rental market, incorporating representative examples from each of two pilot provinces in eastern, central, and western China. The results of this study suggest that the proportion of people leasing farmland increased by approximately 3.9% as a result of land titling, while the rent received increased by about one quarter due to the implementation of this system. Although the effects of this program varied across regions and the hysteresis of land titling was significant, the proportion of people leasing farmland as well as rent increased with increasing implementation time. We, therefore, recommend that the Chinese Central Government continues to implement the LTP across the country, and that farmland maps are utilized to solve disputes caused by the measurement of farmland areas and ambiguous property rights. It will also be necessary to strictly implement the LTP nationwide in order to ensure that both the stability and authority of the policies are not compromised.